An analytical pattern-based method for estimation of a near-surface tornadic wind field. Issue 194 (November 2019) - Chen, Guangzhao; Lombardo, Franklin T.
Abstract: Existing methods of in-situ measurement struggle to capture near-surface wind speeds during a tornado. The demand for accurate near-surface wind fields for the seemingly imminent tornado based design requires new methods of near-surface wind speed estimation, some of which use damage survey data. Information on tree-fall patterns included in damage survey data can and have been used as an indicator of the wind field. Thus, this paper develops an improved analytical method based on tree-fall patterns to estimate the near-surface wind field. This improved analytical model generates a translational steady-state tornado flow field under a superposition of a translational field and a rotational field. The rotational field can be generated by tornado vortex models, then the best-fit parameters for the selected vortex model to create a near-surface translational steady-state tornadic field. This wind field can be estimated on the basis of tornado-induced tree-fall patterns obtained by aerial photos. In this paper, an application is developed with the tree-fall survey data of the 2011 Joplin, MO tornado and used the Rankine vortex model. Highlights: Tornado induced tree-fall patterns can be reproduced by numerical vortex model and preset parameters. The relationship between the tornado induced tree-fall patterns and numerical vortex model can be simplified as an analytical formula. The analytical formula can be widely applied with different vortex models and wind indicators (trees, street sign). Using the analytical formula can reduce the simulation burden and realize the whole wind field with time-dependent vortex parameters.